Development of Financial Accounting Subject Learning Modules Using Learning Management System (LMS) for Students of Class XI Accounting at SMKN 1 Boyolangu - Yuli Ratnasari; Widiyanti Widiyanti; Marsono Marsono (Budapest International Research and Critics University, 2021)
In accounting learning activities in schools, students are still minimal in using modules because there are no modules that are in accordance with student competence. In financial accounting lessons students are required to be able to understand the material and problems that exist for it needs a financial accounting module that can attract students to be active in working on problems in the form of case studies so as to improve the competence of accounting students. The purpose of this research is to design an e-learning-based financial accounting learning module using a learning management system for class XI students at SMKN 1 Boyolangu, know the validity of LMS-based financial accounting learning modules and find out the feasibility level of financial accounting learning modules using class XI learning management system at SMKN 1 Boyolangu. This type of research is Research and Development. 4D development model Thiagarajan, Semmel and Semmel, for the stage of deployment in the scope of smkn 1 boyolangu for accounting majors. The results of the study showed the development process produced the final product in the form of financial accounting modules with materials in odd semesters. Expert feasibility analysis of materials with an average score of 3.94, media expert eligibility of 3.95, eligibility by accounting practitioners 3.95 and student assessment results of modules 3.95. It can be concluded that the modules developed are suitable for use in learning activities.